2000
DOI: 10.1207/s1532785xmep0201_2
|View full text |Cite
|
Sign up to set email alerts
|

Threat and Television Viewing in the United States, 1960-1990

Abstract: We examined people's television viewing choices to determine whether, during times of societal threat, people watch light programming to escape from self, or meaningful programming to explore their fears. Consistent with previous research (Doty, Peterson, & Winter, 1991;Sales, 1973), societal threat was defined as increases in unemployment, consumer price index, prime interest rate, bombings, crime, work stoppages, suicide, homicide, and divorce. The 20 highest rated television programs for each year from 1960… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…The popularity of police dramas and family dramas, for example, appeared negatively correlated with the share of the population over 65 years of age. And the popularity of science fiction varied inversely with unemployment, consistent with research that suggests that people prefer more realistic programming during tough economic times (McIntosh, Schwegler, and Terry‐Murray, ).…”
Section: Resultssupporting
confidence: 73%
“…The popularity of police dramas and family dramas, for example, appeared negatively correlated with the share of the population over 65 years of age. And the popularity of science fiction varied inversely with unemployment, consistent with research that suggests that people prefer more realistic programming during tough economic times (McIntosh, Schwegler, and Terry‐Murray, ).…”
Section: Resultssupporting
confidence: 73%
“…A similar relationship has been found between socioeconomic conditions and television program viewing preferences (McIntosh, Schweigler, & Terry-Murray, 2000). Specifically, researchers rated the top 20 television shows, according to Neilson Ratings, on dimensions of meaningfulness of content, realism of characters and complexity of plot, and compared this to characteristics of societal threat, including increases in unemployment, consumer price index, prime interest rate, bombings, crime, work stoppages, suicide, homicide, and divorce (McIntosh et al, 2000). They found that during times of societal threat, individuals chose to watch television shows that were both meaningful and confronted serious issues.…”
Section: Media Preferences and Social Realitymentioning
confidence: 99%
“…In order to conduct our content analysis of the songs, we created a questionnaire based on the current set of predications and content assessments used in previous archival investigations (i.e., McIntosh et al, 2000). The questionnaire asked raters to consider to what extent the songs explored real, meaningful issues and whether the songs were comforting and romantic.…”
Section: Song Ratingsmentioning
confidence: 99%
“…In the media, social and economic threat has been related to mature facial feature preferences in popular american actresses (Pettijohn & Tesser, 1999) and mature facial feature and larger body size preferences in Playboy Playmates of the Year (Pettijohn & Jungeberg, 2004). McIntosh, Schwegler, and Terry-Murray (2000) had judges rate popular television shows from 1960 to 1990 for meaningfulness of content and found that during times of threat, audiences chose to watch shows that dealt with important issues and had meaningful content, as well as shows with more realistic characters and complex plots. These authors suggest that during threatening social and economic times, individuals may prefer such programs because they offer positive outcomes to complex problems, which may be especially reinforcing under such conditions.…”
Section: Societal Conditions and Social Preferencesmentioning
confidence: 99%
“…We tested our predictions using two lyrical assessment methods: (a) participant ratings of the lyrical content and (b) computer software analysis of song lyrics for thematic content. Similar to the methodology of past research (McIntosh et al, 2000;Pettijohn & Sacco, 2009), we were interested in how individuals' subjective ratings of lyrical content might relate to conditions of economic and social security/insecurity. However, we wanted to extend such an analysis beyond a handful of independent raters to a larger population of participant raters.…”
Section: Environmental Security Hypothesis and Study Predictionsmentioning
confidence: 99%